Extreme Effects of Extreme Disturbances: A Simulation Approach to Assess Population Specific Responses - Reed, Joshua; Harcourt, Robert; New, Leslie; Bilgmann, Kerstin (Frontiers in Marine Science, 2020)
In South Australia, discrete populations of bottlenose dolphins inhabit two large gulfs, where key threats and population estimates have been identified. Climate change, habitat disturbance (shipping and noise pollution), fishery interactions and epizootic events have been identified as the key threats facing these populations. The Population Consequences of Disturbance (PCoD) framework has been developed to understand how disturbances can influence population dynamics. I used population estimates combined with population specific bioenergetics models to undertake a PCoD assessment, comparing how the two populations respond to the identified regional threats. Populations were modeled over a five year period looking at the influence of each disturbance separately. As expected, extreme disturbance scenarios, in terms of frequency and intensity, had the biggest influence on population trends. However, the magnitude of the effect differed by population, with Spencer Gulf showing a 43% and Gulf St Vincent a 23% decline under high frequency and high impact epizootic scenarios. Epizootic events were seen to have the largest influence on population trends and reproductive parameters for both populations, followed by climate change. Modeling provides insights into how disturbances may affect different populations, and informs management to mitigate their potential effects while there is still time to act. Keywords: Bioenergetics, marine mammals, disturbances, bottlenose dolphins, Bayesian modelling, fecundity, population trends Article Impact Statement: Human induced disturbances impact coastal bottlenose dolphins with varying severity depending on the population and disturbance.